Factores que influyen en la sobrevida y pronóstico de pacientes con cáncer de mama invasor operable. - Díaz, Juan (2015)
Clinical and pathological factors related with survival and relapse in 54 patients with clinical stages I and LF breast cancer treated with Halsted mastectomy at Hospital Belen (Trujillo Perú) between January 1966 and December 1982 are studied retrospectively. Up to December 1992, mean follow-up was 165,2 months for the 28 survivors (range 125 to 288 months). Total survival at 10 years was 52,8%. Local recurrence occurred in 20,4% in about 32,6 months. None of the patients with rib wall recurrence survived more than 10 years. Nineteen cases (35,2%) bad distant metastases, most frequently to lungs and lymph nodes. Our findings indicate that age, time of disease,  menopause and localization of tumor did not influence prognosis. Total survival and local or distant metastases bad significant correlation with tumor size and clinical stage. There was inverse relationship between number of positive axillary lymph nodes and survival (p<0,05). Axillary level involved was not significant. We conclude that tumor size, clinical stage and number of axillary lymph nodes involved are prognostic factors related with survival and recurrence in invasive operable breast cancer patients. Treatment strategies have to be based in clear understanding of these factors.